2020
DOI: 10.1063/1.5143212
|View full text |Cite
|
Sign up to set email alerts
|

Predicting fluorescence quantum yields for molecules in solution: A critical assessment of the harmonic approximation and the choice of the lineshape function

Abstract: For the rational design of new fluorophores, reliable predictions of fluorescence quantum yields from first principles would be of great help. However, efficient computational approaches for predicting transition rates usually assume that the vibrational structure is harmonic. While the harmonic approximation has been used successfully to predict vibrationally resolved spectra and radiative rates, its reliability for non-radiative rates is much more questionable. Since non-adiabatic transitions convert large a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
94
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(108 citation statements)
references
References 42 publications
10
94
0
Order By: Relevance
“…[ 142 ] In any case, it is noted that the application of the underlying harmonic approximation for the S 0 potential at such high energies might induce large errors in the calculated rates. [ 247 ] For molecules with comparable molecular (rigid) skeleton, in particular oligomer series such as oligoacenes n Ac (Scheme 3), such approach predicts an increase of k nr with decreasing energy gap between the i and f states (thus for increasing n ). [ 205 ] This “energy gap law” (EGL) was identified as the main reason for the validity of Kasha's rule (emission from S 1 in fluid solution under steady‐state conditions) due to the usually small energy separation found between higher excited states.…”
Section: Molecular Luminescence—intramolecular Processes and Environmental Controlmentioning
confidence: 99%
“…[ 142 ] In any case, it is noted that the application of the underlying harmonic approximation for the S 0 potential at such high energies might induce large errors in the calculated rates. [ 247 ] For molecules with comparable molecular (rigid) skeleton, in particular oligomer series such as oligoacenes n Ac (Scheme 3), such approach predicts an increase of k nr with decreasing energy gap between the i and f states (thus for increasing n ). [ 205 ] This “energy gap law” (EGL) was identified as the main reason for the validity of Kasha's rule (emission from S 1 in fluid solution under steady‐state conditions) due to the usually small energy separation found between higher excited states.…”
Section: Molecular Luminescence—intramolecular Processes and Environmental Controlmentioning
confidence: 99%
“…where IC k is internal conversion (IC) rate constant between electronic states with the same spin multiplicity and ISC k is the intersystem crossing (ISC) rate constant between electronic states with different spin multiplicities [21]. The IC k and ISC k rate constants can be calculated using various softwares at different levels of theory [19,20,[22][23][24][25][26][27]. The most popular method is based on correlation functions for estimating Franck-Condon contributions [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Humeniuk et al assessed the validity of HA for several coumarin dyes when predicting the fluorescence quantum yields in solution. 32 They found that the accuracy of HA for the radiative decay rate is remarkable, while HA will underestimate the IC rates. Hence, HA will lead to an unreliable prediction of fluorescence quantum yield compared to the experiments.…”
Section: Introductionmentioning
confidence: 99%